Dynamic Analysis of Permanent Magnet Synchronous Generator with Power Electronics - Oner, Yasemin; Bekiroglu, Nur; Ozcira, Selin (UNIV SUCEAVA, FAC ELECTRICAL ENG, 2010)
Permanent magnet DC motor-generators (PMDC, PMSG) have been widely used in industrial and energy sectors recently. Power control of these systems can be achieved by controlling the output voltage. In this study, PMDC-PMSG systems are mathematically modeled and simulated in MATLAB&Simulink software. Then the results are discussed. A low power permanent magnet synchronous generator is driven by a permanent magnet DC motor and the output voltage is controlled by a frequency cycle-converter. The output of a half-wave uncontrolled rectifier is applied to an SPWM inverter and the power is supplied to a 300V, 50Hz load. The load which is connected to an LC filter is modeled by state-space equations. LC filter is utilized in order to suppress the voltage oscillations at the inverter output.
Keywords: Permanent Magnet DC Motor; Permanent Magnet Synchronous Generator; Pulse Width Modulation; Computer Science; Engineering